A Case Study of Dissemination of Pigeonpea Cultivation Technology in Hilly Areas of Uttarakhand - R. P. Sahu; M.P. Singh (Indian Journal of Extension Education, 2014)
Pigeonpea is a relatively new crop for north-west Himalayan region of India. The cultivation of Pigeonpea is found to be very beneficial for hilly areas farmers due to its compatibility in major hill farming systems, highly remunerative, capability to tolerate the slight drought condition and need for diversification in hill agriculture. A case study of dissemination of Pigeonpea cultivation technology in hilly area of Bageshwar district of Uttarakhand was conducted during 2008 to 2012. The study covered only rainfed area of three villages namely Karala,Tana and Naghar of Bageshwar block in Bageshwar district. PRA technique was used for the collection of data and information. Before 2008, the area under Pigeonpea cultivation in these villages was nil. After the adoption of Pigeonpea cultivation by the farmers of these villages, the area increased year by year from 0.08 hectare in 2008 to 16.08 hectare in 2012. The benefit:cost ratio of Pigeonpea cultivation was 3.60, which was significantly higher than soybean (1.72), horse gram (1.68), rainfed rice (1.56) and mandua (1.54). There was direct impact of adoption of Pigeonpea cultivation (Var. VLArhar 1) in these three villages, which directly helped in raising the income of the farmers. This impact study also provided the information on the cultivation of Pigeonpea profitability and its effect on farmer’s income. Non-availability of quality seeds (90.0%), insectpest and diseases (83.33%), lack of knowledge of sowing time (76.66%) were the major constraints perceived by the farmers in adoption of Pigeonpea cultivation in these areas.